Acquired Lymphangioma Of Vulva Secondary To Radiotherapy For Carcinoma Cervix - Mehta Vandana; Gupta Sandesh; Shenoi Shrutakirthi D (Wolters Kluwer Medknow Publications, 2003)
Lymphagioma circumscriptum is a rare disorder of lymphatic channels, characterized by occurrence of thin walled frogspawn like vesicles. We report 2 cases of lymphangioma circumscriptum as a late sequel to radiotherapy.